Erratum - in the article: Arsić S, Perić P, Stojković M, Ilić D, Stojanović M, Ajduković Z, Vučić S. Komparativna analiza linearnih morfometrijskih parametara humane mandibule dobijenih direktnim i indirektnim merenjem [Comparative analysis of linear morphometric prameters of the humane mandibula obtained by direct and indirect measurement]. Vojnosanit pregl 2010; 67(10):839-46. - Editorial (Vojnosanitetski Pregled)
This title should have read: Comparative analysis of linear morphometric prameters of the human mandible obtained by direct and indirect measurement. Link to the corrected article 10.2298/VSP1010839A